Juggling Multiple Identities: The Untold Stories Behind a PhD Ethnographic Study. Issue 1 (24th October 2019) - Hou, Junxia; Feng, Anwei
This article explores the fluidity and dynamicity of a Chinese PhD student's research experience in negotiating her identities in a longitudinal ethnographic study, first in China and then in the UK. It adopts retrospective and reflexive document analysis of research journals written by her over a 5-year period of overseas study. The analytical framework for the critical reflection of knowledge production synthesizes key concepts of ontology, epistemology, reflexivity, positionality, serendipity, and intersectionality to describe and interpret the researcher's struggles between insider and outsider, uncertain feelings about different values and beliefs, and emotions due to changing circumstances of family life. The reflexive analysis indicates that PhD students who undertake qualitative studies would function in a far more fluid manner than the often simplistically documented binary roles between an "insider" participant and an outsider researcher in their theses. The article argues that this fluidity in identity shifts and complexity in data collection and analysis are in most cases part and parcel of the research process, which is crucial for researchers to be aware of. Researchers should feel confident to tell the "messy stories" reflexively so as to enhance credibility and trustworthiness of the research findings.